STRATEGI PEMASARAN PERUMAHAN PT. BERLIAN BERSAUDARA PROPERTINDO PALEMBANG: STRATEGI PEMASARAN PERUMAHAN PT. BERLIAN BERSAUDARA PROPERTINDO PALEMBANG - Farid Wadjdi; Pauline Ulviana Siwi, Telly (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
The aim of this research is to find out the Housing Marketing Strategy of PT. Berlian Bersaudara Propertindo Palembang. The approach used in this research is qualitative, namely case studies in organizations. Meanwhile, the nature of this research is exploratory, namely exploring information from informants. The results of the analysis can be concluded that the strategy from the SWOT analysis shows that the company's position is in quadrant I because the internal factor value is 0.88 and the external factor value is 0.27. This shows that the strength factors are greater than the weakness factors and the opportunity factors are slightly greater than the threats faced by the company. The strategy that should be implemented by the company is to support an aggressive growth policy (Growth oriented strategy) so that the strategy used by the company is a W-O strategy. Several things can be recommended, namely: (1) For the level of threat that will occur, namely rising material prices, companies need to survey the prices of building materials in order to get the minimum possible price so as not to harm the company. (2) It is necessary to apply innovation and variation both in terms of house design and to pay attention to available public facilities such as road improvements, irrigation and other public facilities, in this way it can attract consumers.